Matching comparisons of therapeutic efficacy suggest better clinical outcomes for patients treated with peginterferon beta-1a than with glatiramer acetate. (January 2021) - Scott, Thomas F.; Su, Ray; Xiong, Kuangnan; Altincatal, Arman; Castrillo-Viguera, Carmen; Naylor, Maria L.
Background: Peginterferon beta-1a and glatiramer acetate (GA) are approved first-line therapies for the treatment of relapsing forms of multiple sclerosis, but their therapeutic efficacy has not been compared directly. Methods: Clinical outcomes at 2 years, including no evidence of disease activity (NEDA), for patients receiving peginterferon beta-1a 125 mcg every 2 weeks (Q2W) or GA 20 mg/ml once daily (QD) were compared by propensity score matching analysis using individual patient data from ADVANCE and CONFIRM phase III clinical trials. In addition, clinical outcomes at 1–3 years for patients receiving peginterferon beta-1a Q2W or GA 40 mg/ml three times a week (TIW) were evaluated using a matching-adjusted comparison analysis of individual patient data from ADVANCE and the ADVANCE extension study, ATTAIN, and aggregate patient data from the phase III GALA and the GALA extension studies. Results: Propensity-score-matched peginterferon beta-1a patients ( n = 336) had a significantly lower annualized relapse rate [ARR (0.204 versus 0.282); rate ratio = 0.724; p = 0.045], a significantly lower probability of 12-week confirmed disability worsening (10.0% versus 14.6%; hazard ratio = 0.625; p = 0.048), and a significantly higher rate of NEDA (20.3% versus 11.5%; p = 0.047) compared with GA 20 mg/ml QD patients after 2 years of treatment. Matching-adjusted peginterferon beta-1a patients (effective n = 276) demonstrated a similar ARR at 1 year (0.278 versus 0.318; p = 0.375) and significantly lower ARR at 2 years (0.0901 versus 0.203; p = 0.032) and 3 years (0.109 versus 0.209; p = 0.047) compared with GA 40 mg/ml TIW patients ( n = 834). Conclusion: Results from separate matching comparisons of phase III clinical trials and extension studies suggest that peginterferon beta-1a 125 mcg Q2W may provide better clinical outcomes than GA (20 mg/ml QD or 40 mg/ml TIW).